2021
DOI: 10.1177/01455613211009135
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteatoma Surgery With a Dehiscent High Jugular Bulb Treated With Surgery Assisted With Underwater Endoscopy: A Case Report

Abstract: A dehiscent high jugular bulb would be a pitfall in middle ear surgery especially for cholesteatoma. We report a case of cholesteatoma attached to a dehiscent high jugular bulb successfully treated with surgery assisted with underwater endoscopy. To the best of our knowledge, no previous study has reported a case of cholesteatoma with dehiscent high jugular bulb treated with surgery assisted with underwater endoscopy. Owing to the risk of jugular bulb injury, underwater endoscopy is a good indication for middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“… 12 , 13 This technique provides a clear operative field without the need for suction and also protects the inner ear and other important structures, including the JB, from unexpected aeration. 14 In cases of middle ear paragangliomas, significant bleeding can be experienced during surgery because of their vascular nature; thus, underwater endoscopy is appropriate for this case because of continuous blood and bone dust irrigation during suspicious bone drilling in the hypotympanum and around the ICA.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 This technique provides a clear operative field without the need for suction and also protects the inner ear and other important structures, including the JB, from unexpected aeration. 14 In cases of middle ear paragangliomas, significant bleeding can be experienced during surgery because of their vascular nature; thus, underwater endoscopy is appropriate for this case because of continuous blood and bone dust irrigation during suspicious bone drilling in the hypotympanum and around the ICA.…”
Section: Discussionmentioning
confidence: 99%
“…We have already reported the advantage of underwater ear surgery on cholesteatoma with a dehiscent high jugular bulb. 8 These underwater procedures kept a clear view by flushing out blood and dust (bone or tissue) from the operative site. Dähn et al reported the value of transcanal endoscopic surgery for external ear canal cholesteatoma up to Naim stage III.1 Our case was stage III external cholesteatoma placed on the middle posterior wall.…”
Section: Nishiike Et Al Reported a Novel Endoscopic Hydromastoidectomymentioning
confidence: 99%